2008
DOI: 10.1002/ppap.200700175
|View full text |Cite
|
Sign up to set email alerts
|

Selective Surface Modification of Poly(propylene) with OH and COOH Groups Using Liquid‐Plasma Systems

Abstract: Underwater plasma and glow discharge electrolysis are interesting new methods for polymer surface functionalization. The achievable content of O‐containing functional groups exceeds that of oxygen glow discharge gas plasmas by a factor of two (up to ca. 56 O/100 C). The percentage of OH groups among all O‐containing groups can reach 25 to 40%, whereas it is about 10% in the gas plasmas. Addition of hydrogen peroxide increases the fraction of OH groups to at most 70% (27 OH/100 C). The liquid plasma systems are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…[4] The process parameters for generation within underwater capillary discharge, relevance of surface functionalization to the distance of the polymer surface from the plasma source, and a close insight to the concept of selectivity of the process, were studied in depth and discussed elaborately in our earlier communication on the similar topic line. [1] Extension to the same study, herewith presented and discussed, are the effects of addition of hydrogen peroxide on the selectivity of functionalization, and its relevance to underwater plasma process. Selectivity being an output of gas-phase chemical derivatization using Trifluroacetic anhydride, the generated hydroxyl groups on the PP surface using this process under discussion is elaborated in detail.…”
Section: Introductionmentioning
confidence: 92%
“…[4] The process parameters for generation within underwater capillary discharge, relevance of surface functionalization to the distance of the polymer surface from the plasma source, and a close insight to the concept of selectivity of the process, were studied in depth and discussed elaborately in our earlier communication on the similar topic line. [1] Extension to the same study, herewith presented and discussed, are the effects of addition of hydrogen peroxide on the selectivity of functionalization, and its relevance to underwater plasma process. Selectivity being an output of gas-phase chemical derivatization using Trifluroacetic anhydride, the generated hydroxyl groups on the PP surface using this process under discussion is elaborated in detail.…”
Section: Introductionmentioning
confidence: 92%
“…For this purpose, many polymerization techniques [1][2][3][4] have been explored and exhibited the different advantages, in which radiation [5], ultrasonic [6] and plasma [7] syntheses have attracted many researchers. More recent Joshi et al [8] reported an effective selective surface modification by using liquid-plasma system. In addition, for improving the scratch resistance of PMMA the hardcoating techniques have also been studied [9][10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3][4]. A densely functionalized polyolefin surface with preferably monotype functional groups is needed to graft molecules chemically for producing special surface properties as necessary for biochips, sensors, anti-fouling layers, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The exposure of the aliphatic polymer to the UWP that is enriched with OH species (· OH, HO − ) offers greater possibilities to introduce OH groups onto the polymer surface in much higher concentration and with higher (OH) selectivity [1,3] than the treatment in an oxygen gas plasma [12]. Thus, the polymer surface also acts as an OH radical scavenger [7,13,14].…”
Section: Introductionmentioning
confidence: 99%